Aplicación de prezi en el proceso de enseñanza de la asignatura de informática en los octavos años de educación básica del colegio nacional Machala 2013-2014. - García Armijos, Roger Bolívar (2014)
The way of teaching is changing, ICTs are the means that every teacher should be supported through these countless multimedia are helpful tools. This plant research using the prezi application, such as a technological tool that allows us to design presentations on a different level from what we are used with PowerPoint which is the conventional model currently used in the teaching process, in the eighth year basic education, national school Machala, city, province of El Oro in the 2013-2014 academic year.